Island Witch - Jayatissa, Amanda (New York Berkley, 2024)
"Being the daughter of the village Capuwa, or demon-priest, Amara is used to keeping mostly to herself. Influenced by the new religious practices brought in by the British Colonizers, the villagers who once respected her father's craft have turned on the family. Yet, they all still seem to call on him whenever supernatural disturbances arise. Now someone-or something-is viciously seizing upon men in the jungle. But instead of enlisting Amara's father's help, the villages have accused him of carrying out the attacks himself. As she tries to clear her father's name, Amara finds herself haunted by dreams that eerily predict the dark forces on her island. And she can't shake the feeling that it's all connected to the night she was recovering from a strange illness, and woke up, scared and confused, to hear her mother's frantic cries: No one can find out what happened. Lush, otherworldly, and recalling horror classics like Carrie and The Exorcist, Island Witch is a deliciously creepy and darkly feminist tale about the horrors of moral panic, the violent space between girlhood and adulthood, and what happens when female rage is finally unleashed."--
113321
Keywords: Dreams; Demonology; Colonization; Fathers and daughters; Villages; Sri Lanka; Novels; Horror fiction; Gothic fiction; Historical fiction; Paranormal fiction